Assessment of Beneficiary Satisfaction with Community Based Solid Waste Management Service. A case of Okoa Maisha Project in Mnarani Village, Kilifi County, Kenya (International Journal of Scientific Research and Management (IJSRM), 2018)
Abstract Solid Waste Management Service (SWMS) is an important public good, although most local governments in developing countries have failed to effectively provide it to their populace. Ineffective SWMS has serious environmental and public health ramifications. Consequently, other players such as Non-Governmental Organizations (NGOs), private companies and Community Based Organizations (CBOs) have to be involved in the delivery of SWMS. This study assessed the level of beneficiary for households’ satisfaction with SWMS as rendered by Okoa Maisha Project (OMP - the Swahili translation for project of saving lives) operating under the auspices of Where Talent Lives (WTL) - a local CBO located in Mnarani Village in Kilifi County in Kenya. The study revealed that majority of the respondents (52.4%, n=152) were very satisfied with the overall SWMS as rendered by OMP. The satisfaction was mostly due to quality variables such as householders’ education on solid waste management (54%, n=157), neatness of waste collection crew (52.4%, n=152) and reliability of waste collection (49.7%, n=144). Relative to other indicators, the respondents ranked low quality variables such as frequency of waste collection from households and the behaviour of the waste collection crew towards the residents. The study concludes by emphasising on the need for assessment of SWMS as provided by CBOs for improved service delivery. The study recommends routine supervision of the SWMS rendered by donor or government sponsored projects for effective and sustainable service delivery to the beneficiary householders and the community